Determining and Prioritizing Main Factors of Supplier Reliability in Construction Industry - Kayhan, B. Meltem; Cebi, Selcuk; Kahraman, Cengiz (OLD CITY PUBLISHING INC, 2019)
One of the strategic factors in supply chain management is supplier reliability. In particular, the success of the construction project highly depends on the performances of the suppliers since their performance affect quality and cost of any project. Therefore, the reliability of supplier has critical impact on construction project. In the literature, there are dozens of studies that use different models on evaluation of suppliers' performance. Only a few of these studies, however, consider supplier's reliability as a parameter although there are multiple parameters representing the reliability of suppliers. Suppliers' reliability problem should be considered in terms of many factors by leading to a large set of subjective data. In this study, we aim at determining factors which play important role on the reliability of suppliers and analyze the importance degrees of these factors for construction industry. Furthermore, how reliability of a supplier can be measured under the determined factors is illustrated. Prioritizing reliability factors and measuring supplier reliability are hard and complex problems since their solutions are based on subjective and imprecise data sets including uncertainties. For this purpose, Fuzzy Analytic Hierarch Process (FAHP) method is used to prioritize supplier reliability factors while a Fuzzy Inference System (FIS) is used in order to reveal reliability of suppliers' performances.
Keywords: Supplier reliability; Risk assessment; Fuzzy AHP; Fuzzy inference system; DECISION-MAKING APPROACH; SELECTION CRITERIA; MODEL; VIKOR; PERFORMANCE; Computer Science; Science & Technology - Other Topics